Cu3(hexaiminotriphenylene)2: An Electrically Conductive 2D Metal-Organic Framework for Chemiresistive Sensing - Campbell, Michael G.; Sheberla, Dennis; Liu, Sophie F.; Swager, Timothy M.; Dincă, Mircea (Angewandte Chemie International Edition, 2015)
The utility of metal–organic frameworks (MOFs) as functional materials in electronic devices has been limited to date by a lack of MOFs that display high electrical conductivity. Here, we report the synthesis of a new electrically conductive 2D MOF, Cu3(HITP)2 (HITP=2,3,6,7,10,11‐hexaiminotriphenylene), which displays a bulk conductivity of 0.2 S cm−1 (pellet, two‐point‐probe). Devices synthesized by simple drop casting of Cu3(HITP)2 dispersions function as reversible chemiresistive sensors, capable of detecting sub‐ppm levels of ammonia vapor. Comparison with the isostructural 2D MOF Ni3(HITP)2 shows that the copper sites are critical for ammonia sensing, indicating that rational design/synthesis can be used to tune the functional properties of conductive MOFs. A MOF with a nose: Previous efforts to use metal–organic frameworks (MOFs) for chemical sensing have been hindered by poor signal transduction due to a lack of electrical conductivity. A new conductive 2D MOF can be used for the chemiresistive sensing of ammonia. It is shown that the sensing response can be varied by the choice of the metal node.